APLIKASI DOA HARIAN DAN HADITS PILIHAN TKIT BAITUL IMAN SEMARANG MENGGUNAKAN PEMROGRAMAN J2ME (Information Technology and Telematics, 2014)
ABSTRACTInfluential technological developments inall respects, including education. Childrenno longer play on the field but prefer toplay with technology. With thisapplication, children were not onlyintroduced to the game in technology, butthey can also learn from the technology.With the application of daily prayer andhadith this option, the children canmemorize hadith daily prayer and someoptions that fit the curriculum TKIT BaitulIman Semarang. The objectives of thisstudy are expected to facilitate the childrenTKIT Baitul Iman in memorizingindependently without having to be inschool. Children can multiply them by rotememorization heard or read that areavailable in the application. This studyresulted in an application program rotelearning J2ME-based prayer and haditsare fabricated using Netbeans 7.1 that canbe used anywhere and anytime by childrenTKIT Baitul Iman.Keyword: Children, Hadist, J2ME